2016
DOI: 10.1098/rspa.2015.0711
|View full text |Cite
|
Sign up to set email alerts
|

Neutron reflectometry on highly absorbing films and its application to 10 B 4 C-based neutron detectors

Abstract: Neutron reflectometry is a powerful tool used for studies of surfaces and interfaces. The absorption in the typical studied materials is neglected and this technique is limited only to the reflectivity measurement. For strongly absorbing nuclei, the absorption can be directly measured by using the neutron-induced fluorescence technique which exploits the prompt particle emission of absorbing isotopes. This technique is emerging from soft matter and biology where highly absorbing nuclei, in very small quantitie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The results show also that, apart from the near-surface region, the composition is homogenous for both coatings. The compositions of the near-surface regions of comparable B 4 C coatings were closer, as investigated in [45], where it was shown that surface oxidation extends to a maximum of 60 nm into the coatings.…”
Section: Resultsmentioning
confidence: 85%
“…The results show also that, apart from the near-surface region, the composition is homogenous for both coatings. The compositions of the near-surface regions of comparable B 4 C coatings were closer, as investigated in [45], where it was shown that surface oxidation extends to a maximum of 60 nm into the coatings.…”
Section: Resultsmentioning
confidence: 85%
“…The Kapton (ρ = 1.42 g/cm 3 ) is composed of several elements, the macroscopic cross section is Σ mix = i N i σ i , the 10 B 4 C layer (ρ = 2.45 g/cm 3 ) as well. This density differs from the material data and refers to a measured value for the films employed in this detector [27]. The n p calculation for both compounds is reported in table 3.…”
Section: Cross Section and Interaction Probability Calculationmentioning
confidence: 99%
“…It has been shown in [1] that the theoretical efficiency can be reached at an inclination of 10 degrees of the converter layer but it was not possible to prove this agreement at 5 degrees. Moreover, it has been shown in [71] that the inclination of 5 degrees does not affect the neutron detection efficiency due to neutron reflection at the layer surface. The neutron detection efficiency of the Multi-Blade detector at 5 degrees has been measured.…”
Section: Efficiencymentioning
confidence: 99%